Thermal and mechanical properties of polypropylene nanocomposite materials reinforced with cellulose nano whiskers - (:unkn) unknown (WILEY, 2012)
We use polypropylene (PP, an apolar polymer) and cellulose nano whiskers (CNW, a polar material) to produce nano polymer composites with enhanced mechanical and thermal properties. To improve compatibility, maleic anhydride grafted PP has also been used as a coupling agent. To enhance the uniform distribution of CNW in the composite, the matrix polymer is dissolved in toluene, and sonification and magnetic stirring are applied. Good film transparency indicates uniform CNW dispersion, but CNW domains in the composite film observed under an scanning electron microscope may indicate slight agglomeration of CNW in the composite film. The tensile strength of the composite compared with neat PP improves by 70-80% with the addition of CNW. The crystallinity has also been improved by about 50% in the CNW reinforced samples. As the content of CNW increases, the composite exhibits higher thermal degradation temperature, higher hydrophilicity, and higher thermal conductivity. (C) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: polypropylene; cellulose nano whiskers; maleic anhydride; nano composite; mechanical properties; SUSPENSIONS; FIBERS